2004
DOI: 10.1063/1.1691017
|View full text |Cite
|
Sign up to set email alerts
|

Two- and three-body photodissociation of gas phase I3−

Abstract: The photodissociation dynamics of I 3 Ϫ from 390 to 290 nm ͑3.18 to 4.28 eV͒ have been investigated using fast beam photofragment translational spectroscopy in which the products are detected and analyzed with coincidence imaging. At photon energies р3.87 eV, two-body dissociation that generates I Ϫ ϩI 2 (A 3 ⌸ 1u ) and vibrationally excited I 2 Ϫ (X 2 ⌺ u ϩ )ϩI( 2 P 3/2 ) is observed, while at energies у3.87 eV, I*( 2 P 1/2 )ϩI 2 Ϫ (X 2 ⌺ u ϩ ) is the primary two-body dissociation channel. In addition, three-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…These translational energy distributions are similar to those from the lower absorption band of I − 3 , where the two-body channels blended seamlessly into the corresponding three-body channels, 14 and suggest that two-and three-body dissociation occur via the same dynamical process. Specifically, at 4.13 eV, the Br( 2 P 3/2 ) + I − 2 (X 2 + u ) and I − ( 1 S) + IBr channels (1B, 2A, 2B, and 2C) all correlate to channel 3B in the limit of maximum internal excitation of the diatomic fragment, and the two-body P(E T ) distributions all feature sharp falloffs at E min T .…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…These translational energy distributions are similar to those from the lower absorption band of I − 3 , where the two-body channels blended seamlessly into the corresponding three-body channels, 14 and suggest that two-and three-body dissociation occur via the same dynamical process. Specifically, at 4.13 eV, the Br( 2 P 3/2 ) + I − 2 (X 2 + u ) and I − ( 1 S) + IBr channels (1B, 2A, 2B, and 2C) all correlate to channel 3B in the limit of maximum internal excitation of the diatomic fragment, and the two-body P(E T ) distributions all feature sharp falloffs at E min T .…”
Section: Discussionmentioning
confidence: 62%
“…It is interesting that no evidence for similar sequential three-body dissociation has been observed in I − 3 , either in our group 13,14 or others. 15,16 While we only tentatively assigned an I − ( 1 S) + I 2 (B 3 + 0u ) product channel, Nakanishi 15 assigned the channel at nearly the same photon energy (4.28 and 4.27 eV, respectively) with a branching fraction of 0.11.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Geppert et al reported evidence for a four-body breakup in the DR of C 2 D 5 [18], though this was not the dominant channel. It is noted that multiple fragmentation has also been seen in several different types of reaction processes [19][20][21] and is not exclusive to DR.…”
mentioning
confidence: 99%
“…Even within this relatively small system, there is a wealth of interactions that probe nearly all aspects of the SBI. The I 3 − anion dissociates into various iodine-containing fragments 7,8 upon photoexcitation to either of its two major absorption bands (labelled C and D in Fig. 1b).…”
mentioning
confidence: 99%